Mixed layer depth values for the n = 1968 modern dinocyst database extracted from the World Ocean Atlas 2018, Argo floats data 2005-2017 - Xiner Wu (PANGAEA, 2025)
Monthly, seasonal and annual mixed layer depth (MLD) values at the 1968 sites of the modern dinocyst database by de Vernal et al. (2020). The MLD values were extracted from the World Ocean Atlas 2018 (WOA18) objectively analyzed mean field of Argo floats data of 2005-2017 using a density threshold of 0.125 kg/m3 with reference to 10 m depth. In order to get an MLD value that corresponds to each site, the MLD climatology products were interpolated to the previously published 1968 sites.
In: Wu, X (2025): Mixed layer depth values for the n = 1968 modern dinocyst database [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982265